Gasdermin D–mediated pyroptosis suppresses liver regeneration after 70% partial hepatectomy. Issue 9 (4th May 2022) - Lv, Xingyu; Chen, Jiang; He, Jiayan; Hou, Lidan; Ren, Yiyue; Shen, Xiaoyun; Wang, Yifan; Ji, Tong; Cai, Xiujun
Abstract: Pyroptosis is a kind of programmed cell death primarily mediated by gasdermin D (GSDMD) and shown to regulate multiple diseases. However, its contribution to liver regeneration, a fine‐tuned tissue repair process mediated primarily by hepatocytes after mass loss, remains unclear. Herein, we found that caspase‐11/GSDMD‐mediated pyroptosis was activated in regenerating liver after 70% partial hepatectomy. Impeding pyroptosis by deleting GSDMD significantly reduced liver injury and accelerated liver regeneration. Mechanistically, GSDMD deficiency up‐regulates the activation of hepatocyte growth factor/c‐Met and epidermal growth factor receptor mitogenic pathways at the initiation phase. Moreover, activin A and glypican 3 (GPC3), two terminators of liver regeneration, were inhibited when GSDMD was absent. In vitro study suggested the expressions of activin A and GPC3 were induced by interleukin (IL)–1β and IL‐18, whose maturations were regulated by GSDMD‐mediated pyroptosis. Similarly, pharmacologically inhibiting GSDMD recapitulates these phenomena. Conclusion: This study characterizes the role of GSDMD‐mediated pyroptosis in liver regeneration and lays the foundation for enhancing liver restoration by targeting GSDMD in liver patients with impaired regenerative capacity. Abstract : we identify GSDMD‐mediated pyroptosis suppresses liver regeneration after 70% partial hepatectomy. Retarded activation of EGFR and HGF/c‐met pathways and accelerated termination of liver regeneration via IL18/GPC3 and IL1β/activin A/smad2 axis contribute to the biological function of GSDMD in this process.image